2021
DOI: 10.3390/vaccines9060623
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccines for Genitourinary Tumors: Recent Progresses and Future Possibilities

Abstract: Background: In the last years, many new treatment options have widened the therapeutic scenario of genitourinary malignancies. Immunotherapy has shown efficacy, especially in the urothelial and renal cell carcinomas, with no particular relevance in prostate cancer. However, despite the use of immune checkpoint inhibitors, there is still high morbidity and mortality among these neoplasms. Cancer vaccines represent another way to activate the immune system. We sought to summarize the most recent advances in vacc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 120 publications
0
17
0
Order By: Relevance
“…Immune therapy is the most widely used treatment for many cancers, and its effect is associated with the expression of checkpoint genes [ 35 ]. Although PCa is an immune desert tumor, some studies have suggested the usefulness of immunotherapy for PCa [ 36 , 37 ]. Therefore, we compared the expression levels of checkpoint genes between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Immune therapy is the most widely used treatment for many cancers, and its effect is associated with the expression of checkpoint genes [ 35 ]. Although PCa is an immune desert tumor, some studies have suggested the usefulness of immunotherapy for PCa [ 36 , 37 ]. Therefore, we compared the expression levels of checkpoint genes between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…In the second line, the combination of pembrolizumab with ramucirumab achieved an ORR of 13% [ 66 ]. Other agents, such as vaccines, epigenetic modulators (e.g., Enhancer of zeste homolog 2 (EZH2) inhibitors), ADC, and poly-ADP ribose polymerase (PARP) inhibitors, represent potentially effective ways to improve ICIs efficacy [ 67 , 68 ]. Preliminary results of phase I/II trials of ICIs combined with anti-FGFR agents show an ORR of 11–30% in pre-treated patients, reaching 54% in the first-line case [ 69 , 70 , 71 , 72 ] ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“… 73 Recently, data from animal models have suggested that TAMs critically contribute to vaccine-induced tumor regressions. 74 We identified 35 trials focused on the combination of vaccination with TAM-targeted therapies, whether as an adjuvant or combined into the vaccine to enhance the therapeutic benefit of the vaccine and reduce the adverse effects. Most of these trials are in Phase I or I/II; only 5 have reached Phase II, all of which are evaluating a TLR3 agonist, poly-ICLC.…”
Section: Trends In the Clinical Trials Of Combination Therapymentioning
confidence: 99%